Assessment of NETest Clinical Utility in a U.S. Registry‐Based Study. (29th August 2018) - Liu, Eric; Paulson, Scott; Gulati, Anthony; Freudman, Jon; Grosh, William; Kafer, Sheldon; Wickremesinghe, Prasanna C.; Salem, Ronald R.; Bodei, Lisa
Abstract: Background: The clinical relevance of molecular biomarkers in oncology management has been recognized in breast and lung cancers. We evaluated a blood‐based multigene assay for management of neuroendocrine tumors (NETs) in a real‐world study (U.S. registry NCT02270567). Diagnostic accuracy and relationship to clinical disease status in two cohorts (treated and watch‐and‐wait) were evaluated. Materials and Methods: Patients with NETs ( n = 100) were followed for 6–12 months. Patients' primary tumors were gastroenteropancreatic (68%), lung 20%, and of unknown origin (12%). Characteristics included well‐differentiated, low‐grade tumors (97%), stage IV disease (96%); treatment with surgery (70%); and drug treatment (56%). NETest was measured at each visit and disease status determined by RECIST. Scores categorized as low (NETest 14%–40%) or high (≥80%) defined disease as stable or progressive. Multivariate analyses determined the strength of the association with progression‐free survival (PFS). Results: NETest diagnostic accuracy was 96% and concordant (95%) with image‐demonstrable disease. Scores were reproducible (97%) and concordant with clinical status (98%). The NETest was the only feature linked to PFS (odds ratio, 6.1; p < .0001). High NETest correlated with progressive disease (81%; median PFS, 6 months), and low NETest correlated with stable disease (87%; median PFS, not reached). In the watch‐and‐wait cohort, low NETest was concordant with stable disease in 100% of patients, and high NETest was associated with management changes in 83% of patients. In the treated cohort, all low NETest patients (100%) remained stable. A high NETest was linked to intervention and treatment stabilization (100%). Use of NETest was associated with reduced imaging (biannual to annual) in 36%–38% of patients. Conclusion: Blood NETest is an accurate diagnostic and can be of use in monitoring disease status and facilitating management change in both watch‐and‐wait and treatment cohorts. Abstract : Neuroendocrine tumors (NETs), or carcinoids, comprise a spectrum of tumors that arise from neuroendocrine cells lining the gut and lung or that are present in the pancreas. Using a U.S. registry, this study examined the clinical utility of biomarker assays for management of neuroendocrine tumor disease. Diagnostic accuracy and relationship to clinical disease status in two cohorts was evaluated, and the results are reported in this article.